2020
DOI: 10.26434/chemrxiv.11816841.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mass Spectral Similarity Mapping Applied to Fentanyl Analogs

Abstract: <b>: </b>This manuscript outlines a straight-forward procedure for generating a <i>map</i> of similarity between spectra of a set. When applied to a reference set of spectra for Type I fentanyl analogs (molecules differing from fentanyl by a single modification), the map illuminates clustering that is applicable to automated structure assignment of unidentified molecules. An open-source software implementation that generates mass spectral similarity mappings of unknowns against a librar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In terms of novel data analysis and interpretation, Gilbert et al demonstrated how principal component analysis can be used for the classification of fentanyl analogues based on their gas chromatography mass spectrometry (GC‐MS) spectra [34]. Moorthy et al showed the ability to use GC‐MS data combined with hybrid similarity searching [35] and mass spectral similarity mapping to identify previously unseen analogs [36].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of novel data analysis and interpretation, Gilbert et al demonstrated how principal component analysis can be used for the classification of fentanyl analogues based on their gas chromatography mass spectrometry (GC‐MS) spectra [34]. Moorthy et al showed the ability to use GC‐MS data combined with hybrid similarity searching [35] and mass spectral similarity mapping to identify previously unseen analogs [36].…”
Section: Introductionmentioning
confidence: 99%